The Image of the House and the Family Thought in L.N.Tolstoy's Novel "War And Peace" - Israilova G.R. (Zien Journals, 2022)
The article studies Tolstoy's poetics in the novel "War and Peace" as "the image of the house" and "family thought". When considering the epic novel in the works of Leo Tolstoy, it was noted that the authornarrator, endowed with antinomian thinking, creates a system of figurative and semantic oppositions that allows you to immerse yourself in the mobile world and family destinies, which is an important component in revealing the characters of the characters and understanding the author's position in relation to them.
Keywords: human; image of home; traditions of realism